Steps toward behavioural weight loss and maintenance: a daily practice - Adam, Gareeballah O. (International Journal Of Community Medicine And Public Health, 2022)
Obesity is an increased fat accumulation to the levels that affect health and wellbeing. Body mass index (BMI) categorizes people as normal, overweight or obese depending on arithmetic equations. Obesity is a global epidemiological problem, affecting more than 30% of the world population. The main hazard is that the obesity prevalence still escalating. Human behavior plays a major role in the causes of obesity. In addition, other factors are also contributing to bodyweight increase such as, genetic, endocrine and metabolic factors. Nevertheless, obesity can be controlled and ideal weight can be achieved. Some measures and practices were suggested in this mini-review through which a one-day human life cycle was set up as a model that can be followed to ensure proper weight and maintain it thereafter. These measures include regular sleep/wake-up pattern, strict timing of meals, practicing exercise, drinking at least 2.5 liters of water and early going to bed. However, the fundamental mechanisms of weight loss and increase were not addressed in this mini-review.